Endobronchial Ultrasound Transbronchial Needle Aspiration for the Diagnosis of Paratracheal and Peribronchial Central Parenchymal Lesions - Nikolay Yanev; Evgeni Mekov; Dimitar Kostadinov (Folia Medica, 2020)
Objectives: Obtaining qualitative, sufficient material for the diagnosis of malignancies in cases with normal endoscopic findings in patients with suspected lung cancer and hilar and mediastinal lymphadenopathy is challenging.Materials and methods: Endobronchial ultrasound (EBUS) was used to control a transbronchial needle biopsy (ТBNA) for the first time in our country. From 2015 to 2018, TBNA with a convex probe EBUS was performed on 57 patients [41 men, 16 women, mean age 56.10 (range 37-77 years)] with mediastinal lesions found on CT scan. We used the Hitachi Aloka - ProSound Alpha 7 and BF-UC180F (Olympus) 21G and 22G needles Ultrasound System. In 22 of the cases, we performed a biopsy of hilum lesions (9 on the left and 13 on the right), in 13 - of subcarinal lesions, and in 4 - of lesions located on the right paratracheal lymphatic chain. Results: EBUS-TBNA confirmed lung cancer in 48 patients (84.2%). In 33 of them, it was non-small cell lung cancer: spinocellular in 13 cases and adenocarcinoma in 17 cases; three cases were without accurate verification. Small cell lung cancer was found in 15 cases. In two cases, the biopsies were negative for tumor (3.5%), and in seven - non-specific inflammatory process (12.3%). Conclusions: This study confirms the high diagnostic success rate of EBUS-TBNA reported in similar studies developed on a daily routine basis without adhering to a specific protocol. EBUS-TBNA is an interventional procedure with high sensitivity in diagnosing hilar and mediastinal lesions in negative conventional bronchoscopy and thus is useful in patients with paratracheal and peribronchial lesions. The results could be improved with training and experience.